Development of double carrier modulation / differential detection technique (DCM/Diff.D) - Jacklyn Andrew Alam (Universiti Malaysia Perlis, 2008)
A new transmission and detection technique namely Double Carrier Modulation/ Differential Detection (DCM/Diff.D) are represented. The performance between the DCM/Diff.D techniques with the existing system, Wavelength Division Multiplexing (WDM) technique is compared. This new scheme show how the Differential Detection technique improves the system performance significantly, it also demonstrate that this technique overcomes the problems associated with voltage threshold in conventional systems, and how it suggest the possibility to double up the conventional long distances without amplifiers. It will be shown subsequently that DCM/Diff.D will improve the probability of error and extend the distance to more than twice kilometer significantly longer than that being the conventional approach. The data rate used is 2.5Gbps and 10Gbps with 0dBm transmit power.